Australia New Zealand Closer Economic Relations Trade Agreement (ANZCERTA) and Regional Integration - Scollay, Robert; Findlay, Christopher; Kaufmann, Uwe (ISEAS Publishing, 2010)
The origins, evolution and impact of the Australia New Zealand Closer Economic Relations Trade Agreement are examined in this book. ANZCERTA is often referred to as a benchmark for trade agreements. Not only does the book examine the agreement and how it evolved, but it also provides lessons for others, particularly in ASEAN, as they work on regional on bilateral economic relations. The special features of the Agreement are identified, and its evolution is charted. Current debates are reviewed, and assessments of its impact are discussed. Ten lessons for the designers of other agreements are presented
Description based on online resource; title from PDF title page (publisher's Web site, viewed 22. Jun 2018)